Evaluation of dexmedetomidine, tiletamine, and zolazepam for the immobilization of black bears. (27th March 2015) - Coltrane, Jessica A.; Farley, Sean; Saalfeld, David; Battle, David; Carnahan, Tony; Teisberg, Justin
ABSTRACT Telazol® (TZ, tiletamine hydrochloride [HCl] and zolazepam HCl) has been used to immobilize black bears for research and management activities since the 1980s. Although considered an effective and safe drug, TZ has some disadvantages, including prolonged restraint time and inability of reversal. We tested the efficacy of dexmedetomidine and Telazol® (dexMTZ) to immobilize 9 urban black bears (Ursus americanus) in Anchorage, Alaska, USA, during 2013. We recorded induction and recovery times and measured physiological responses of partial pressures of arterial carbon dioxide (PaCO2) and oxygen (PaO2), lactate, percent oxygen saturation of hemoglobin, and HCO3 in relation to anesthesia. Immobilization was rapid in all bears with good dart placement, and bears maintained a deep level of anesthesia throughout the duration of processing (<1 hr). Bears did not exhibit any altered thermoregulatory ability; body temperatures remained relatively constant and normothermic (36.3 °C–39.2 °C). Mean heart rate (67 ± 13 beats/min) was within the normal range for black bears at 60–90 beats/min, and no instances of tachycardia were observed. We observed normal respiration rates (18 ± 5 breaths/min) and high oxygen saturations in black bears. Within 24 min postinjection oxygen saturation remained above 90%. Immobilization did not appear to disrupt acid–base balance in bears, and administration of atipamezole provided relatively quick and complete recovery of all bears captured. Our results indicate that dexMTZ provides a safe and effective means to immobilize black bears for research and management activities. © 2015 The Wildlife Society.